2015
DOI: 10.1111/xen.12212
|View full text |Cite
|
Sign up to set email alerts
|

Rapid hepatic perfusion decellularization: technique and critique

Abstract: Liver perfusion decellularization technique using both 0.8% Triton X-100 and 0.8% SDS is a simple and rapid technique, yielding efficiently decellularized liver matrices preserving their vascular integrity, 3D architecture and 68% of total collagen content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Constant flow pressure rather than constant flow rate was infrequently used [7,8]. Gravity-based perfusion was also reported [9]. An approach of lower SDS concentration with longer perfusion duration or gradually increasing concentration was advocated [10,11], aiming at minimizing the damage to ECM and remnant detergent contents in the decellularized scaffold.…”
Section: Xenotransplantation -New Insightsmentioning
confidence: 99%
See 3 more Smart Citations
“…Constant flow pressure rather than constant flow rate was infrequently used [7,8]. Gravity-based perfusion was also reported [9]. An approach of lower SDS concentration with longer perfusion duration or gradually increasing concentration was advocated [10,11], aiming at minimizing the damage to ECM and remnant detergent contents in the decellularized scaffold.…”
Section: Xenotransplantation -New Insightsmentioning
confidence: 99%
“…Studies demonstrated the use of livers from various animal species for decellularization including rats [10,[25][26][27], mice [13], ferrets [28,29], rabbits [9,30,31], sheep [14,21], and swine [8,11,[32][33][34]. Decellularization of whole porcine liver was first reported by Matthiesen et al [2].…”
Section: Xenotransplantation -New Insightsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fathi et al. propose a technique for decellularizing the caudate haptic lobes of rabbits to scaffold to create a transplantable liver. The detergent‐based technique is low‐cost, efficient, and preserved vascular integrity.…”
Section: Basic Sciencementioning
confidence: 99%